2014
DOI: 10.7314/apjcp.2014.15.18.7489
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: Biogenesis, Roles for Carcinogenesis and as Potential Biomarkers for Cancer Diagnosis and Prognosis

Abstract: MicroRNAs (miRNAs) are short non-coding RNAs of 20-24 nucleotides that play important roles in carcinogenesis. Accordingly, miRNAs control numerous cancer-relevant biological events such as cell proliferation, cell cycle control, metabolism and apoptosis. In this review, we summarize the current knowledge and concepts concerning the biogenesis of miRNAs, miRNA roles in cancer and their potential as biomarkers for cancer diagnosis and prognosis including the regulation of key cancer-related pathways, such as ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 100 publications
(98 reference statements)
1
33
0
3
Order By: Relevance
“…miRNAs are mainly involved in the regulation of genes related to cell fate, especially in the development-related genes; however, almost no relevant genes that maintain the basic activities of cells have miRNA target sites (20). In the present study, we found that mangiferin specifically increased the expression of miR-15b in the U87 glioma cells.…”
Section: Discussionsupporting
confidence: 58%
“…miRNAs are mainly involved in the regulation of genes related to cell fate, especially in the development-related genes; however, almost no relevant genes that maintain the basic activities of cells have miRNA target sites (20). In the present study, we found that mangiferin specifically increased the expression of miR-15b in the U87 glioma cells.…”
Section: Discussionsupporting
confidence: 58%
“…Предполагается, что под их контролем находится около 60 % всех протеин-кодирующих генов [12]. Искажение работы системы микроРНК-зависимого посттранскрипционного контроля генов, определя-ющих активность пролиферации и апоптотическую готовность [13], метаболический статус [14], взаимо-действие с межклеточным матриксом и адгезивные характеристики [15], происходит в процессе злокаче-ственной трансформации и усугубляется в ходе про-грессии опухоли.…”
Section: том 2 обзорные статьиunclassified
“…So far, there are about 1424 miRNAs in human, 720 in mouse, and 408 in rat which were confirmed by miRBase datebase (Kozomara and Griffiths-Jones, 2011). It is known that hundreds of miRNAs participate in various biological phenomena, such as cell proliferation, development, differentiation and metabolism (Kavitha et al, 2014). As a special one among them, the miR-29b has unexceptionally become a hot topic.…”
Section: Introductionmentioning
confidence: 98%